2019
DOI: 10.26599/jnr.2019.9040007
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors of early neurological deterioration in isolated acute lacunar infarction in basal ganglia

Abstract: Objective:To investigate, in basal ganglia, the factors associated with early neurological deterioration (END) of isolated acute lacunar infarction.Methods:167 patients, in the retrospective group, with isolated acute lacunar infarction in basal ganglia, were defined by magnetic resonance imaging (MRI). The National Institutes of Health Stroke Scale (NIHSS) defined early neurological deterioration as increases of ≥ 2 within 72 hours following admission. Baseline variables predicting END were investigated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Regarding motor function, the extent of damage to the basal ganglia seems to be a neural correlate for motor deficit. Three studies included in this review reported that the lesion locations were primarily in the basal ganglia [32,34,35], which is in line with the theory that a common ischemic stroke in deep brain regions featured by high disability rate is basal ganglia lacunar stroke [43]. Thus, it can be speculated that limb motor dysfunction of included ischemic stroke patients was mainly related to basal ganglia impairment.…”
Section: The Involvement Of the Basal Ganglia And Insula Insupporting
confidence: 64%
“…Regarding motor function, the extent of damage to the basal ganglia seems to be a neural correlate for motor deficit. Three studies included in this review reported that the lesion locations were primarily in the basal ganglia [32,34,35], which is in line with the theory that a common ischemic stroke in deep brain regions featured by high disability rate is basal ganglia lacunar stroke [43]. Thus, it can be speculated that limb motor dysfunction of included ischemic stroke patients was mainly related to basal ganglia impairment.…”
Section: The Involvement Of the Basal Ganglia And Insula Insupporting
confidence: 64%
“…Besides, the RDW is also an independent risk factor of venous thromboembolism [ 24 ]. Hence, the association of the RDW with mortality in patients with AIS may be related to a pro-thrombotic mechanism [ 25 ]. Meanwhile, several studies reported that a higher RDW is related to malnutrition, which can result in poor outcomes in patients with AIS, especially in elderly individuals [ 9 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Along similar lines, Chan et al [21] stated that the length of stay was higher in AIS patients with anemia on admission than in nonanemic ones. Some researchers explained that anemic patients tend to experience relatively high incidence of complications during their stay in hospital [22][23][24]. However, there was absence of significant difference for in-hospital mortality and length of stay between normal hemoglobin group and mild anemia group, which may due to rela- tively large proportion of older patients complicated with mild anemia or should be consider another cutoff for anemia in oldest older.…”
Section: Discussion/conclusionmentioning
confidence: 99%